Stunting in Focus: Unraveling the Trends and Prevalence Among Children in Maluku Utara Province (2019-2023) - Sukmawati Hasan, Diana; Muhammad, Sinta (PT. Sangadji Media Publishing, 2023)
Maluku Utara, an Indonesian province with captivating natural landscapes, cultural richness, and abundant resources, faces a pressing issue of stunting among children. Stunting, a chronic condition affecting growth and development, poses a significant public health challenge. This study examines stunting trends in Maluku Utara from 2019 to 2023, emphasizing its consequences on physical and cognitive development. Despite national targets to reduce stunting, Maluku Utara encounters unique challenges. This research aims to uncover the specific context by analyzing trends, identifying high-prevalence regions, and exploring contributing factors. The study's significance lies in informing targeted interventions and policies tailored to Maluku Utara's conditions, aiding progress toward national reduction goals. Utilizing quantitative methods, the research relies on secondary data from the Ministry of Health of the Republic of Indonesia, applying descriptive statistical analysis. The four-year data reveals fluctuations in stunting prevalence, with a resurgence in 2023, particularly in Halmahera Utara District. District-level analysis exposes disparities, emphasizing the need for continuous and focused efforts, especially in high-prevalence areas. This research addresses knowledge gaps, providing insights into stunting dynamics, and facilitating culturally sensitive interventions. By understanding trends and underlying factors, stakeholders can formulate effective strategies to combat stunting in Maluku Utara, contributing to broader national efforts for a healthier and more prosperous future for the region's children.